Open Source Software and Growth of Linux: The Indian Perspective - Suman, Yogesh; Bhardwaj, A.K. (DESIDOC Journal of Library & Information Technology, 2003)
The purpose of this article is to present and analyse the recent trends in development of Linux as operating system. It identifies the problems encountered and examines the factors, which might play an important role in its future growth. It is pointed out that while proprietary software like Windows dominates the market in desktop personal computers (PCs), Linux is fast becoming a popular choice as number one server operating system for enterprises because of its flexibility and low cost of ownership. It is predicted that by year 2005, Linux will capture almost 50% of global market as enterprise operating system. The authors conclude that because of its cost effectiveness and flexibility to change, Linux can be a powerful tool in bridging the gap of digital divide in India. http://dx.doi.org/10.14429/dbit.23.6.3612